Xenia per Roberto Pettorino Xenia for Roberto Pettorino - Roberto Delle Donne (Fuori Collana, 2017)
Roberto Pettorino was born in Naples on April 24, 1946. After graduating in Physics at the University of Naples Federico II in 1970, he later pursued research at Stanford's SLAC and Geneva's CERN. He was Full Professor of Theoretical Physics at the Faculty of Physical, Mathematical and Natural Sciences at Federico II University, Dean of the Faculty from 2007 to 2012, President of the University Assessment Team since October 2012. Since the first Open Archive was created by Paul Ginsparg in 1991 at the Los Alamos National Laboratory (LANL preprint archive, USA) for the elementary particle physics community, Roberto Pettorino was engaged in promoting Open Access. Since 2002, he had been delegated by the Rector of Naples Federico II for the libraries information services and member of the Scientific Technical Council of the Information Services Center; then he chaired the Permanent Commission for Libraries and Digital Resources. In 2002-2003 he promoted the development of the Digital Library of the University of Naples Federico II. Here are some contributions, collected to celebrate Roberto Pettorino's memory on April 8, 2013 when the Library Center was officially named after him.